2009
DOI: 10.1007/s00404-009-1052-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fetal asphyxia in intrahepatic cholestasis of pregnancy

Abstract: In this study, it has been demonstrated that for the evaluation of fetal status, increased TBA levels in the mother and increased exposure time for the fetus to these increased values of TBA within the maternal circulation system help to predict increased risk of asphyxia in newborns to ICP mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 20 publications
2
19
0
2
Order By: Relevance
“…22,23 In a recent retrospective study, TBA levels and the duration of exposure to elevated bile acids were identified as independent variables for predicting asphyxia. 21 This is consistent with the findings of Glantz et al, 2 who demonstrated an association between severe ICP and asphyxial events.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…22,23 In a recent retrospective study, TBA levels and the duration of exposure to elevated bile acids were identified as independent variables for predicting asphyxia. 21 This is consistent with the findings of Glantz et al, 2 who demonstrated an association between severe ICP and asphyxial events.…”
Section: Discussionsupporting
confidence: 90%
“…Asphyxial events have been reported to occur frequently in ICP. 2,3,10,21 Bile acids have been shown to induce vasoconstriction of placental vessels, which may lead to acute hypoxia seen in stillborn fetuses. 5 In rats, bile acid derivatives have also been shown to cause cardiac dysfunction, which might be the cause of sudden deterioration of fetal cardiotocography.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought that maternal serum bile acid levels and fetal bile acid exposure time [16,17,18] are important prognostic factors in ICP. Our results showed that plasma CRH was negatively correlated with TBA and ALT in ICP patients, and there was a stronger correlation with TBA.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The incidence of meconium staining of amniotic fluid in normal term pregnancy is approximately 15% and is considered to be a sign of foetal distress. 5 In ICP incidence of meconium staining of amniotic fluid has been reported to be 16-58%. ICP have reported a perinatal mortality of 10-15%.…”
Section: Causes Of Jaundice or Deranged Liver Function Tests Specificmentioning
confidence: 99%